Pemanfaatan Google Sites untuk Administrasi Terpadu di Institut Teknologi dan Bisnis (ITB) Semarang - Cantik Padmasari; Raihan Maulana Adi Artanta; Nur Aeni Fatimah; Andika Prihantara; Heri Usodo (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to improve the quality of integrated administration at the Semarang Institute of Technology and Business (ITB) through the use of Google Sites as an easily accessible and efficient information management platform. Activities include gathering needs, developing content structures, training on Google Sites, and providing implementation support. The results demonstrate improved information accessibility, streamlined document management, and faster administrative processes. The use of Google Sites provides an alternative solution that supports transparent, integrated, and technologically adaptive administrative services. In the future, the use of this platform can be expanded into other academic and operational activities. With this technology, ITB Semarang can further streamline internal and external communication processes and support faster and more accurate decision-making. This program is also expected to serve as a model for other educational institutions in adopting technology to improve administrative efficiency. Furthermore, it is hoped that the use of this technology will also increase the participation and involvement of the entire academic community in managing information more effectively.